2018
DOI: 10.22159/ajpcr.2018.v11s1.26605
|View full text |Cite
|
Sign up to set email alerts
|

Color Changes of Post-Debonding White Spot Lesion After Microabrasion Technique With Fluoride and Casein Phosphopeptide-Amorphous Calcium Phosphate Application

Abstract: Objective: The prevalence of enamel demineralization among patients after orthodontic treatment is about 50%, which begins with the formation of white spot lesions. The presence of these lesions causes esthetic problems. The aim of this study was to quantify the color changes in post-debonding white spot lesions after microabrasion technique with fluoride and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) application. Materials and Methods:This study used 42 first premolar teeth that had been extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
1
1
3
Order By: Relevance
“…This is consistent with the finding by Anggani et al, which concluded that CPP-ACP application enhanced the esthetic of white spot lesions because of CPP-ACP's ability to fill the subsurface enamel pores. This supporting study applied CPP-ACP once/a day for 14 days [29]. Alternatively, our finding is in disagreement with a different study that stated the inability of CPP-ACP application to enhance the esthetic of post-debonding white spot lesions and correlated that to the short duration of CPP-ACP application, which was only once with follow-up after 6 weeks [30].…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with the finding by Anggani et al, which concluded that CPP-ACP application enhanced the esthetic of white spot lesions because of CPP-ACP's ability to fill the subsurface enamel pores. This supporting study applied CPP-ACP once/a day for 14 days [29]. Alternatively, our finding is in disagreement with a different study that stated the inability of CPP-ACP application to enhance the esthetic of post-debonding white spot lesions and correlated that to the short duration of CPP-ACP application, which was only once with follow-up after 6 weeks [30].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have been done on fluoride's effect on enamel remineralization (Table 1). Tooth decay that begins with a white spot lesion can be controlled with fluoride therapy (FT) [Anggani et al, 2021]. Fluoride can increase the strength of tooth enamel and prevent the acidic solubility of enamel and dentin.…”
Section: The Effect Of Fluoridementioning
confidence: 99%
“…Dentre os tratamentos para as LMB, tem-se disponíveis aqueles não invasivos, ou seja, que não resultam em remoção de estrutura dentária, tais quais aqueles remineralizadores (Schwendicke et al, 2019). Os mais comuns são a aplicação profissional de fluoreto em concentrações mais altas que as encontradas nos dentifrícios e bochechos de uso caseiro, seja ele na forma de gel, verniz ou espuma, que, independentemente da forma, irá potencializar o processo de remineralização (Knösel et al, 2007;Fernández-Ferrer et al, 2018;Dai et al, 2019;Anggani et al, 2021); e ainda, tem-se disponível o Fosfopeptídeo de Caseína com Fosfato de Cálcio Amorfo (CPP-ACP), no qual o paciente realiza autoaplicação, guiada pelo cirurgião-dentista. O CPP-ACP corresponde a um agente bioativo derivado do leite, que funciona como uma reserva de cálcio e fosfato, deixando o meio supersaturado diante uma queda de pH.…”
Section: Odontologia De Mínima Intervenção (Omi)unclassified
“…Por fim, considera-se que os tratamentos remineralizadores apresentados são capazes de remineralizar as LMB, contudo, não há evidência suficiente que mostre sua efetividade na melhoria estética (Anggani et al, 2021), sendo ainda, a literatura controversa em relação ao melhor tipo de tratamento remineralizador (Abdullah;John, 2016). Ademais, ressalta-se que alternativas microinvasivas parecem produzir melhor resultado estético, comparados àqueles não invasivos (Pliska et al, 2012;Youssef et al, 2020;Anggani et al, 2021).…”
Section: Odontologia De Mínima Intervenção (Omi)unclassified
See 1 more Smart Citation